Reconstruction of the Paradigm of State Land Tenure After the Constitutional Court Decision 181/PUU-XXII/2024 - Ulul Albab; Aura Pasharellla; Cinta Afifah Farid; Dwi Wirayudha; Dzikri Al Ghifari (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2026)
This article examines the paradigm shift in state land governance, with a special focus on agrarian-forestry management in relation to indigenous peoples, in accordance with the Constitutional Court Decision No. 181/PUU-XXII/2024. Using a reflective-normative juridical approach, this study identifies a fundamental transformation in the interpretation of State Control Rights, shifting from a dominium-based model to an agrarian framework oriented towards public trust. Theoretically, this research contributes by formulating the concept of Agrarian Public Trust as a synthesis between the HMN doctrine and the public trust doctrine, repositioning the state as a trustee rather than the absolute owner of natural resources. Normatively, this study shows that the interpretation of the Constitutional Court mandates a reconfiguration of the legal relationship between the state and indigenous peoples, especially by recognizing subsistence-based customary practices as constitutional protection and by limiting the use of criminal sanctions in agrarian-forestry governance. Furthermore, this study provides concrete institutional recommendations, including: (1) harmonization of agrarian and forestry regulations through an integrated legal framework that is in line with the principles of public trust; (2) the establishment of a National Coordinating Board for Agrarian Governance to unify data, policies, and dispute resolution mechanisms; and (3) the creation of a special trust-based institution for the recognition, verification, and protection of customary territories. These measures are essential to ensure legal certainty, prevent criminalization, and advance substantive agrarian justice in Indonesia.